1988
DOI: 10.1056/nejm198806093182304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Immunosuppressive Regimens in Cadaver Renal Transplantation: Long-Term Cyclosporine, Short-Term Cyclosporine Followed by Azathioprine and Prednisolone, and Azathioprine and Prednisolone without Cyclosporine

Abstract: We conducted a randomized trial in seven Australian hospitals of the efficacy and safety of three immunosuppressive regimens after first transplantation of a cadaver kidney: long-term cyclosporine, short-term (three months) cyclosporine followed by azathioprine and prednisolone, and azathioprine and prednisolone without cyclosporine. Patients assigned to long-term cyclosporine (n = 138) or short-term cyclosporine followed by azathioprine and prednisolone (n = 141) had similar actuarial 12-month survival (98.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…The primary and secondary outcomes of the study-death-censored graft survival, patient survival, and the combined end point of death or graft loss 4,5,18 -have previously been reported. Cancer outcomes were prespecified in the original trial and were briefly reported at 15 and 20 years 4,5 but were not previously analyzed and reported in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary and secondary outcomes of the study-death-censored graft survival, patient survival, and the combined end point of death or graft loss 4,5,18 -have previously been reported. Cancer outcomes were prespecified in the original trial and were briefly reported at 15 and 20 years 4,5 but were not previously analyzed and reported in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the trial, including the extent of deviations from protocol therapy, have been previously reported 4,5,18 but will be summarized in brief here.…”
Section: Concise Methodsmentioning
confidence: 99%
“…As minimizing immunosuppression is presumed to be beneficial, clinical trials were performed using conversion studies from CsA to AZA or MMF, avoiding or tapering one of the immunosuppressive drugs [6][7][8][9][10]12,13,30].…”
Section: Discussionmentioning
confidence: 99%
“…nephrotoxicity and hypertension [2,4,5]. To minimize these side effects, and in an attempt to preserve benefits on graft survival, administration of CsA for one year and thereafter, conversion to the less nephrotoxic drugs AZA [6][7][8][9][10] or mycophenolate mofetil (MMF) [10], would be an option. To reduce the long-term side effects (cancer) [11] of immunosuppressive agents, and to improve the quality of life after transplantation, the AZA, MMF or prednison (Pred) dose can be tapered [10,12,13], provided this is not accompanied by rejection.…”
Section: Introductionmentioning
confidence: 99%
“…The major advantage was a reduction in the number of acute rejections and improvement in 1-year graft survival [8,12,481. Its impact on medium-and long-term graft survival has not been firmly established [ll].…”
Section: Introductionmentioning
confidence: 99%